A Novel Synthetic Nano-Catalyst (Ag2O3/Zeolite) for High Quality of Light Naphtha by Batch Oxidative Desulfurization Reactor - Amer Talal Nawaf; Shymaa Ali Hameed; Layth T. Abdulateef; Aysar Talib Jarullah; Mohammed S. Kadhim; Iqbal M. Mujtaba (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
Oxidative desulfurization process (ODS), enhanced with a novel metal oxide (Ag ions) as an active component over nano-zeolite that has not been reported in the literature, is used here to improve the fuel quality by removing mercaptan (as a model sulfur compound in the light naphtha). Nano-crystalline (nano-support (Nano-zeolite)) composite is prepared by Incipient Wetness Impregnation method loaded with a metal salt to obtain 0.5, 1 and 1.5% of Ag2O3 over Nano-zeolite. The new homemade nano-catalysts (Ag2O3/Nano-zeolite) prepared are characterized by Brunauer–Emmett–Teller (BET) (surface area, pore volume and pore size), X-ray Diffraction (XRD), Fourier Transform Infra Red (FTIR), and Scanning Electron Microscopy (SEM) analysis. The ODS process is then used to evaluate the performance of the catalysts for the removal of sulfur at different reaction temperatures (80–140 °C) and reaction times (30–50 min) in a batch reactor using the air as oxidant. 87.4% of sulfur removal has been achieved using 1% silver oxide loaded on Nano zeolite (1% of Ag2O3/Nano-zeolite) giving a clear indication that our newly designed catalyst is highly efficient catalyst  in the removal of sulfur compound (mercaptan) from naphtha. A new mechanism of chemical reaction for sulfur removal by oxygen using the new homemade catalyst (Ag2O3/Nano-zeolite) prepared has been suggested in this study. The best kinetic model parameters of the relevant reactions are also estimated in this study using pseudo first order technique based on the experimental results. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).